«Hard to Be a God»: the Evolution of Political Images of Vladimir Putin - Ekaterina Dmitrievna Zabrodkina; Veronika Vladimirovna Pasynkova (Управленческое консультирование, 2018)
The article focuses on the transformation of political images of the Russian President Vladimir Putin. A political image is defined as a combination of representations of a political leader, which circulate in the public informational discourse. The authors consider the evolution of Putin’s political images during three periods: 1) 2000-2008; 2) 2008-2012; 2012 - present. The article aims at revealing main components of Putin’s political images as President and Prime-Minister of the Russian Federation. The authors refer to the discourse analysis (textual and visual analysis) of the empirical materials and the social-constructivist approach. The empirical material of the article include academic and journalist publications, articles and interviews published by Russian mass-media, official texts and videos of Russia’s politicians, statistical data and surveys’ results, as well as photos and documentaries.